2020
DOI: 10.3389/fimmu.2020.584950
|View full text |Cite
|
Sign up to set email alerts
|

How Ancestry Influences the Chances of Finding Unrelated Donors: An Investigation in Admixed Brazilians

Abstract: associated with reduced chances of finding a match (up to 60% reduction). Finally, we document that the strongest reduction in chances of finding a match is associated with having an MHC region of exclusively African ancestry (up to 75% reduction). We apply our findings to a specific condition, for which there is a clinical indication for transplantation: sickle-cell disease. We show that the increased African ancestry in patients with this disease leads to reduced chances of finding a match, when compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 66 publications
0
25
0
2
Order By: Relevance
“…Given that matching for transplantation requires identity over multiple HLA loci, the higher haplotypic Would increasing the proportion of individuals with African ancestry in the registries increase the chances of patients with a greater African ancestry finding a compatible donor? Nunes et al [47] showed that individuals with a higher proportion of African ancestry in the MHC on average find proportionally more donors identified as 'Black' or 'Mixed' (figure 6b). This suggests that, for individuals with greater African ancestry, an increase in the proportion of donors with African ancestry will contribute to their chances of finding a compatible donor.…”
Section: Human Leucocyte Antigen Diversity and Bonemarrow Transplanta...mentioning
confidence: 99%
See 3 more Smart Citations
“…Given that matching for transplantation requires identity over multiple HLA loci, the higher haplotypic Would increasing the proportion of individuals with African ancestry in the registries increase the chances of patients with a greater African ancestry finding a compatible donor? Nunes et al [47] showed that individuals with a higher proportion of African ancestry in the MHC on average find proportionally more donors identified as 'Black' or 'Mixed' (figure 6b). This suggests that, for individuals with greater African ancestry, an increase in the proportion of donors with African ancestry will contribute to their chances of finding a compatible donor.…”
Section: Human Leucocyte Antigen Diversity and Bonemarrow Transplanta...mentioning
confidence: 99%
“…What are the consequences of the large differences in allele frequencies between geographic regions (figure 5) to the chances of finding a matching donor in a repository? Nunes et al [47] quantified how an individual's ancestry influences their chances of finding a matching donor in REDOME, the Brazilian bone-marrow donor registry. Surveying over 8000 admixed individuals, they showed that those who self-identify as 'Black' have a reduction in their chances of finding a matching donor, with respect to those who self-identify as 'White'.…”
Section: Human Leucocyte Antigen Diversity and Bonemarrow Transplanta...mentioning
confidence: 99%
See 2 more Smart Citations
“…7 In a recent study of the Brazilian UD reg is try (REDOME), this proba bil ity was <10% for sickle cell dis ease patients. 8 In addi tion, access to searching for and using UD grafts is lim ited by financial issues even in dif fer ent areas of high-income countries (HICs). In the US, Paulson et al found that patients with leu kemia from poorer areas were less likely to undergo UD allo-HCT com pared to patients from wealth ier countries.…”
Section: Factors Affect Ing Access To Allo-hct (Figure 4) Donor Avail Abil Itymentioning
confidence: 99%